2017
DOI: 10.3390/f8090321
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Climate Change and Land Use Impacts to Explore Forest Conservation Policy

Abstract: This study uses a scenario-based approach to ask what are the varying impacts to forest extent and biodiversity from sixteen climate change and forest conversion scenario combinations, and what do they suggest about future forest conservation policy directions? We projected these combinations onto existing forests in South Korea and grouped them into four forest categories. We used species distribution models for 1031 climate vulnerable plant species as a biodiversity index, and found that species richness los… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 45 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…In addition, many species are expected to shift their ranges in response to shifting climates and biogeochemical drivers [ 57 ]. Therefore, conservation planning also needs to consider the impacts of future climate scenarios [ 58 , 59 ]. Although this study only considered species’ current suitable environments, focusing on climate vulnerable species in designating additional PAs would be one of the climate mitigation activities for conserving ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, many species are expected to shift their ranges in response to shifting climates and biogeochemical drivers [ 57 ]. Therefore, conservation planning also needs to consider the impacts of future climate scenarios [ 58 , 59 ]. Although this study only considered species’ current suitable environments, focusing on climate vulnerable species in designating additional PAs would be one of the climate mitigation activities for conserving ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…Tropical forests, home to a disproportionate amount of the world's biodiversity, are experiencing some of the largest declines (França et al, 2020;Hansen et al, 2013;IPBES, 2019;Song et al, 2018). Land use change is the leading cause of forest declines worldwide (Choe & Thorne, 2017;FAO & UNEP, 2020;Ostberg et al, 2015;WWF, 2020) with recent estimates, suggesting that only 24% of tropical forests are still intact (Lewis et al, 2015). In addition, there is an increasing concern regarding the impacts of climate change, with research suggesting that its effects could be already eclipsing those of land use change on 60% of the global land surface (Ostberg et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Our study also found high species richness of rarity classes and of nationally listed endangered and endemic species in each rarity class in these mountains (Figure and Figure ), which indicates our simple approach can identify high biodiversity areas for rare species. We suggest that further field surveys in these areas could help identify high priority plant conservation areas, that biological monitoring focused on tracking populations of narrow geographic range plant species be implemented in the northeastern parts of South Korea, and that regional urban development and land use plans should consider the preservation of the high biodiversity in this area (Choe & Thorne, ).…”
Section: Discussionmentioning
confidence: 99%